Czech EdTech Startup Expansion to the Republic of Korea - Tlapák, Matouš; Kubíček, Aleš; Carter, Michael; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2017)
The paper investigates if an international educational start-up company based in the Czech Republic should expand to the Republic of Korea and suggests the best means for the foreign country expansion.The thesis has two main parts. The first one provides a theoretical framework for a foreign marketing expansion strategy and introduces necessary information about the chosen country, including its demographics, socio-economic and cultural aspects.The following part suggests the mode of entry, positioning & marketing mix adjustments based on the country specifics, a proposal of marketing communication plan and a go-to-market strategy. Towards the end of the paper financial figures of the intended market entry are revealed and recommendations for potential future growth outlined.
Vedoucí práce: Aleš Kubíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses